Uji Konsentrasi Ekstrak Biji Bintaro (Cerbera manghas L.) terhadap Mortalitas Scotinophara coarctata Fabricius pada Tanaman Padi Sawah - Salbiah, Desita; Rasfita, Riza Winda (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2024)
Rice is a staple food crop in Indonesia that contains nutrients such as carbohydrates, protein, fat, fiber, and vitamins. Efforts to increase rice production still experience obstacles such as Scotinophara coarctata Fabricius pest attacks which can cause yield losses of 35% if the reaches the economic threshold clump of rice plants. Plants that have the potential as botanical pestiside are bintaro plants (Cerbera manghas L). This research aims to obtain the concentration of bintaro (Cerbera manghas L) seed extract that is effective against Scotinophara coarctata Fabricius mortality. This research was conducted at the Laboratory of Plant Pests, and Experimental Garden of the Faculty of Agriculture, University of Riau, from December 2023 to March 2024, using a completely randomized design (CRD) consisting of 6 treatments and 4 replications. Treatment applications consists of concentrations of 0 g.l-1 water, 20 g.l-1 water, 40 g.l-1 water, 60 g.l-1 water, 80 g.l-1 water, and 100 g.l-1 water. The results showed that different concentrations had a significant effect on the mortality of Scotinophara coarctata. The concentration of 60 g.l-1 water is an effective concentration in controlling S. coarctata nymphs because it can cause total mortality of 80% with the initial time of death 18.50 hours after application and lethal time 50 at 58.25 hours after application.